PENINGKATAN HASIL BELAJAR EKOLOGIS TENTANG PENCEMARAN LINGKUNGAN MELALUI PEMBELAJARAN BERBASIS MASALAH BAGI SISWA KELAS X MIPA 2 SMA NEGERI 1 BULU PADA SEMESTER 2 TAHUN PELAJARAN 2018/2019 - Eko Hartono (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
The purpose of this study is to improve: (1) the quality of ecological learning about Environmental Pollution through problem-based learning, (2) analyzing the improvement of ecological learning outcomes about Environmental Pollution through problem-based learning. This research is a class action research. The research design uses the Kemmis & Tagart stages which consist of 4 stages (1) planning, (2) implementation, (3) observation, and (4) reflection. The research sample was students of class X MIPA 2 in SMA Negeri 1 Bulu in the 2018/2019 academic year. Data collection techniques using test and questionnaire techniques. Data analysis techniques using descriptive analysis.The problem based learning model (PBM) can improve student learning outcomes. This can be seen in the first cycle there is an increase to 75%, and in the second cycle to 100% with indicators of achievement of learning achievement that exceeds the stipulated 80% of students with a minimum score of 75. (2) Ecological competence of students in learning shows an increase in grades an average of 61.64 in the first cycle to 70.39 in the second cycle. Conclusions (1) the quality of learning is indicated by the learning process by using a questionnaire with indicators of the number of students 75% have good criteria. (2) ecological learning outcomes for students in problem-based learning can improve student learning outcomes in Biology subjects can be seen in increasing mastery learning in the pre cycle only reached 3.7% in the first cycle the value of classical completeness reached 75% and the value of classical completeness in cycle II reached 100%